Role of Village Government Policy Innovation: Mediating Influence of Promotion on Tourism Development in Sumenep - Raden Khaeru Ahmadi; Rachmad Hidayat; Sri Rahayu; Rifda Fitrianty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of promotion on tourism development by considering village government policy innovation as a mediating variable. The research focused on three leading tourist destinations in Sumenep Regency, namely Matahari Beach, Semaan Tourism Village, and Kedatim Mangrove Tourism. These three locations were chosen because they have high natural tourism potential and are a priority for local village government development. The method used in this study is Structural Equation Modeling - Partial Least Squares (SEM-PLS), which allows for the simultaneous and comprehensive testing of causal relationships between variables. A total of 100 respondents were used as research samples, consisting of the community, tourism managers, and village stakeholders who are directly involved in tourism development. The results of the study show that promotion has a positive and significant influence on tourism development. In addition, promotion has also been proven to have a positive and significant influence on policy innovation carried out by village governments. Policy innovation itself also shows a positive influence on tourism development. However, village government policy innovation is not able to be a significant mediating variable between tourism promotion and development. This finding shows that although promotion and policy innovation each contribute to the progress of the tourism sector, the effectiveness of innovative policies still requires the support of other factors such as community participation, cross-sector collaboration, and more structured and data-based long-term planning.